2023
DOI: 10.3390/polym15173618
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of Silver Content on the Antibacterial and Biological Properties of Poly(ɛ-caprolactone)/Biphasic Calcium Phosphate 3D-Scaffolds for Bone Tissue Engineering

Francesca Menotti,
Sara Scutera,
Bartolomeo Coppola
et al.

Abstract: There is a growing interest in tissue engineering, in which biomaterials play a pivotal role in promoting bone regeneration. Furthermore, smart functionalization can provide biomaterials with the additional role of preventing orthopedic infections. Due to the growing microbial resistance to antimicrobials used to treat those infections, metal ions, such as silver, thanks to their known wide range of bactericidal properties, are believed to be promising additives in developing antibacterial biomaterials. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Conversely, besides the 3D structure, the scaffolds developed here are characterized by hierarchal porosity, where the micro- and macro-porosity have a synergic effect on osteointegration and osteogenesis, as required in bone tissue engineering [ 28 , 29 , 30 ]. In our previous research, we demonstrated that PCL and BCP/PCL can be added along with different antimicrobials—both silver and essential oils—without affecting their higher interconnected porosity [ 6 , 10 , 11 ]. Similarly, in research by Sadiasa and colleagues in 2014, the structure of a 3D scaffold based on poly(L-lactic acid) (PLLA) and PCL was evaluated; increased porosity and pore size were observed, particularly when PLLA was added [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Conversely, besides the 3D structure, the scaffolds developed here are characterized by hierarchal porosity, where the micro- and macro-porosity have a synergic effect on osteointegration and osteogenesis, as required in bone tissue engineering [ 28 , 29 , 30 ]. In our previous research, we demonstrated that PCL and BCP/PCL can be added along with different antimicrobials—both silver and essential oils—without affecting their higher interconnected porosity [ 6 , 10 , 11 ]. Similarly, in research by Sadiasa and colleagues in 2014, the structure of a 3D scaffold based on poly(L-lactic acid) (PLLA) and PCL was evaluated; increased porosity and pore size were observed, particularly when PLLA was added [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we revealed that silver introduced at 1.67% into PCL-based 3D scaffolds significantly affects Saos-2 cell viability [ 10 ]; thus, we reduced its concentration to ~1%. Subsequently, when the silver content was decreased, the Saos-2 cells were viable and, additionally, proliferated into the constructs [ 6 ]. For these reasons, the following experiments were performed on PCL-based specimens with the lowest silver concentrations, which were 0.79% and 1% for the 3D scaffolds pored with NaNO 3 and NaCl, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An experimental BCP formulation has been proven capable of reliably eluting antibiotics [ 152 ]; combinations with silver ions [ 153 , 154 ] or chitosan [ 143 , 155 ] have also demonstrated antimicrobial properties. In the research of Chen et al [ 143 ], even though no testing was performed on bacterial cells, their compound promoted osteoblast differentiation and activity; this can have important implications given the interplay between osteoblasts and bacterial infections [ 156 , 157 , 158 , 159 ] ( Table 3 ).…”
Section: Biomaterials Compatible With Antibiotic Infusionmentioning
confidence: 99%